Whole-genome resequencing and bisulfite sequencing provide new insights into the feeding habit domestication in mandarin fish (Siniperca chuatsi) - Li, Ling; He, Shan; Lin, Ming-Hui; Zhang, Yan-Peng; Kuhl, Heiner; Liang, Xu-Fang (Frontiers in Genetics, 2023)
Mandarin fish (Siniperca chuatsi) is one of the most economically important fish in China. However, it has the peculiar feeding habit that it feeds solely on live prey fish since first-feeding, while refuses dead prey fish or artificial diets. After the specific training procedure, partial individuals could accept dead prey fish and artificial diets. The genetic basis of individual difference in artificial diet feeding habit is still unknown. In the present study, the resequencing was performed between 10 individuals which could be domesticated to accept artificial diets and 10 individuals which could not. Through the selective sweep analysis based on heterozygosity (Hp) and population differentiation coefficient (Fst), 57 candidate windows were identified as the putative selected regions for feeding habit domestication of mandarin fish, involved in 149 genes. These genes were related to memory, vision and olfaction function, which could be potential targets of molecular marker assistant breeding of artificial diet feeding trait. Beside of the DNA sequence, we also explored the potential role of DNA methylation in feeding habit domestication in mandarin fish. Whole-genome bisulfite sequencing was performed between the individuals which could be domesticated to accept artificial diets and those could not. 5,976 differentially methylated regions were identified, referring to 3,522 genes, such as the genes involved in cAMP signaling pathway. The DNA methylation changes of these genes might contribute to the adaption of artificial diets in mandarin fish. In conclusion, the putative selected regions and the differentially methylated regions were identified in the whole genome, providing new insights into the feeding habit domestication from live prey fish to artificial diets in mandarin fish. And the involved genes were identified as the candidate genes for molecular breeding of artificial diet utilization in mandarin fish.